Seasonal abundance of major sucking and chewing insects of guava (Bangladesh Journal of Zoology, 2019)
Seasonal abundances of the sucking insects, namely mealy bug, white fly and scale insects, and chewing insect viz., fruit fly was monitored during September, 2016 to June, 2017 in a guava Psidium guajava orchard. Sucking insect was monitored by weekly observation on the leaves and chewing insect was captured using methyl eugenol trap. The mealy bug, white fly and scale insects were abundant during 4th week of November to 4th week of January and they showed fluctuations in their population. The mealy bug, white fly and scale insects had peak abundance in the 1st week of January, 4th week of November and 1st week of December, respectively. The scale insect revealed significantly higher abundance compared to other sucking insects. Two species of fruit fly, namely Bactrocera tryoni and B. dorsalis were found in the guava orchard and B. tryoni showed significantly higher abundance compared to B. dorsalis both in winter and summer seasons. In winter, B. tryoni reached the peak abundance in the 2nd week of January and their peak abundance in summer occurred in the 1st week of May. The daily mean temperature and relative humidity influenced the abundance of the sucking and chewing insects. Temperature individually contributed 30.0, 59.6, 59.3% abundance and temperature with relative humidity had 34.8, 60.9 and 73.5% abundance on mealy bug, white fly and scale insect, respectively. The effect of temperature on the abundance of fruit fly in winter and summer were 42.6 and 50.3%, respectively and the combined effect of temperature with relative humidity were 68.7% in winter and 61.9% in summer.Bangladesh J. Zool. 47(1): 97-105, 2019